Nickel Coordination Chemistry with Oxothiolate Ligands and Its Relevance to Hydrogenase Enzymes - Chou, Jun-Hong; Varotsis, Constantinos; Kanatzidis, Mercouri G. (My University, 1995)
The coordination chemistry of several new nickel complexes with multidentate oxo/thiolate ligands, in relation with the active site problem of hydrogenase enzymes, is described. Structural, spectroscopic and electrochemical data are reported and discussed.
Keywords: Electron paramagnetic resonance; Sulfur atom; Nickel complex; Select bond distance; Resonance Raman Spectrum